2016
DOI: 10.1177/0969733016654317
|View full text |Cite
|
Sign up to set email alerts
|

Moral sensitivity, moral distress, and moral courage among baccalaureate Filipino nursing students

Abstract: Results of the study imply that moral distress is a reality among all healthcare professionals including nursing students and requires more consideration by nurse educators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
131
0
22

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(163 citation statements)
references
References 45 publications
10
131
0
22
Order By: Relevance
“…Thus, nursing students experience morally distressing situations and they witness circumstances of care and behavior that are morally inappropriate in the academic environment, disrespect to the subjects and their rights, incompatible with their values, principles and personal standards learned during their academic training, possibly experiencing moral distress (MD). Studies on MD in nursing students have been prominent in the international (1,(3)(4)(5)(6)(7) and national (8)(9)(10) fields. In this context, students may face difficulties to resist disciplinary mechanisms of power, which aim to form docile bodies with maxims of obedience and submission to norms and hierarchy (11) .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, nursing students experience morally distressing situations and they witness circumstances of care and behavior that are morally inappropriate in the academic environment, disrespect to the subjects and their rights, incompatible with their values, principles and personal standards learned during their academic training, possibly experiencing moral distress (MD). Studies on MD in nursing students have been prominent in the international (1,(3)(4)(5)(6)(7) and national (8)(9)(10) fields. In this context, students may face difficulties to resist disciplinary mechanisms of power, which aim to form docile bodies with maxims of obedience and submission to norms and hierarchy (11) .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that personal and professional factors(Suhonen et al, 2011), organizational culture, and leadership style(Escolar, 2018), can affect moral courage in nurses. It appears that ethical climate of organization also affects moral courage (Höge et al, 2019; Suhonen et al, 2011).…”
mentioning
confidence: 99%
“…2,17 Moral courage has been studied from the perspective of nursing students also earlier, mainly in the 2000s. 5,9,12,14,17 It has been shown that students feel an obligation to act as patients' advocates, 12,17 and for this, they need moral courage. 9,14,17 However, students sometimes seem to lack courage.…”
Section: Introductionmentioning
confidence: 99%